Transcriptomic Analysis of Mature Transgenic Poplar Expressing the Transcription Factor JERF36 Gene in Two Different Environments - Zhang, Weixi; Wang, Yanbo; Zhang, Tengqian; Zhang, Jing; Shen, Le; Zhang, Bingyu; Ding, Changjun; Su, Xiaohua (Frontiers in Bioengineering and Biotechnology, 2022)
During the last several decades, a number of transgenic or genetically modified tree varieties with enhanced characteristics and new traits have been produced. These trees have become associated with generally unsubstantiated concerns over health and environmental safety. We conducted transcriptome sequencing of transgenic Populus alba × P. berolinensis expressing the JERF36 transcription factor gene (ABJ01) and the non-transgenic progenitor line (9#) to compare the transcriptional changes in the apical buds. We found that 0.77% and 1.31% of the total expressed genes were significant differentially expressed in ABJ01 at the Daqing and Qiqihar sites, respectively. Among them, 30-50% of the DEGs contained cis-elements recognized by JERF36. Approximately 5% of the total number of expressed genes showed significant differential expression between Daqing and Qiqihar in both ABJ01 and 9#. 10 DEGs resulting from foreign gene introduction, 394 DEGs that resulted solely from the environmental differences, and 47 DEGs that resulted from the combination of foreign gene introduction and the environment were identified. The number of DEGs resulting from environmental factors was significantly greater than that resulting from foreign gene introduction, and the combined effect of the environmental effects with foreign gene introduction was significantly greater than resulting from the introduction of JERF36 alone. GO and KEGG annotation showed that the DEGs mainly participate in the photosynthesis, oxidative phosphorylation, plant hormone signaling, ribosome, endocytosis, and plant-pathogen interaction pathways, which play important roles in the responses to biotic and abiotic stresses ins plant. To enhance its adaptability to salt-alkali stress, the transgenic poplar line may regulate the expression of genes that participate in the photosynthesis, oxidative phosphorylation, MAPK and plant hormone signaling pathways. The crosstalk between biotic and abiotic stress responses by plant hormones may improve the ability of both transgenic and non-transgenic poplars to defend against pathogens. The results of our study provide a basis for further studies on the molecular mechanisms behind improved stress resistance and the unexpected effects of transgenic gene expression in poplars, which will be significant for improving the biosafety evaluation of transgenic trees and accelerating the breeding of new varieties of forest trees resistant to environmental stresses.